Rancangan Proyek Penguatan Profil Pelajar Pancasila (P5) Bagi Sekolah Dasar Marsudirini Gedangan Semarang - Hartutik, Hartutik; Astuti, Andarweni; Priyanto, Agustinus Sugeng; Jelahu, Timotius Tote (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
An implementation of the ”Kurikulum Merdeka Belajar”, especially the implementation of the ”Proyek Penguatan Profil Pelajar Pancasila (P5)”  at Marsudirini Elementary School, Gedangan Semarang, has not been optimal. It happens because teachers still have difficulty designing P5. This service activity aims to guide teachers in designing the “Proyek Penguatan Profil Pelajar Pancasila (P5)” at Marsudirini Elementary School, Gedangan Semarang. Therefore, the material provided in this service is the dimensions of the “Profil Pelajar Pancasila (P3)” and the “Proyek Penguatan Profil Pelajar Pancasila (P5)”. The methods used in this service are lectures, questions, and answers, and practice. The results of this service activity are P5 designs for several themes, namely the Local Wisdom Theme, the Bhinneka Tunggal Ika Theme, the Sustainable Lifestyle Theme, and the Entrepreneurship Theme. Of these themes, the P5 topic designs that were successfully designed for Marsudirini Elementary School Gedangan Semarang were Shining Regional Culture, Love Myself Campaign, Save Water, Love the Environment, My School is Comfortable, My Attitude is Polite, Waste is a Blessing for a Brighter Life, and Hydroponic Vegetables.